Nanoplasmonic electron acceleration by attosecond-controlled forward rescattering in silver clusters - Passig, Johannes; Zherebtsov, Sergey; Irsig, Robert; Arbeiter, Mathias; Peltz, Christian; Goede, Sebastian; Skruszewicz, Slawomir; Meiwes-Broer, Karl-Heinz; Tiggesbaeumker, Josef; Kling, Matthias F.; Fennel, Thomas (Nature Communications, 2017)
In the strong-field photoemission from atoms, molecules, and surfaces, the fastest electrons emerge from tunneling and subsequent field-driven recollision, followed by elastic backscattering. This rescattering picture is central to attosecond science and enables control of the electron's trajectory via the sub-cycle evolution of the laser electric field. Here we reveal a so far unexplored route for waveform-controlled electron acceleration emerging from forward rescattering in resonant plasmonic systems. We studied plasmon-enhanced photoemission from silver clusters and found that the directional acceleration can be controlled up to high kinetic energy with the relative phase of a two-color laser field. Our analysis reveals that the cluster's plasmonic near-field establishes a sub-cycle directional gate that enables the selective acceleration. The identified generic mechanism offers robust attosecond control of the electron acceleration at plasmonic nanostructures, opening perspectives for laser-based sources of attosecond electron pulses.
CRIS-Team Scopus Importer:2023-04-20